2008
DOI: 10.1090/memo/0917
|View full text |Cite
|
Sign up to set email alerts
|

The stable manifold theorem for semilinear stochastic evolution equations and stochastic partial differential equations

Abstract: This article is a sequel to [M.Z.Z.1] aimed at completing the characterization of the pathwise local structure of solutions of semilinear stochastic evolution equations (see's) and stochastic partial differential equations (spde's) near stationary solutions. Stationary solution are viewed as random points in the infinite-dimensional state space, and the characterization is expressed in terms of the almost sure long-time behavior of trajectories of the equation in relation to the stationary solution. More speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 38 publications
1
119
0
Order By: Relevance
“…In the case of SPDEs, this property does not hold. In [16], applying the unstable manifold theorem ( [23]), we can still deduce the IHSIEs in the infinite dimensional case.…”
Section: It Is Well Known Thatmentioning
confidence: 99%
“…In the case of SPDEs, this property does not hold. In [16], applying the unstable manifold theorem ( [23]), we can still deduce the IHSIEs in the infinite dimensional case.…”
Section: It Is Well Known Thatmentioning
confidence: 99%
“…In 1945, Ulam and Neumann [40] pointed out the importance of random dynamical systems. In the last thirty years, the research of random dynamical systems is further expanded especially in the field of stochastic differential equations and stochastic partial differential equations in a series of work such as [4,23,24,28,31]. Pathwise stationary solution and random periodic solution are two central concepts in the study of random dynamical systems [4,13,14,21,20,29,31,36,37,42,43,44].…”
Section: The Problemmentioning
confidence: 99%
“…We will only sketch the proof. Details may be found in [19]. Using the Oseledec integrability condition (2.2) and the Ruelle-Oseledec theorem ([19, Theorem 2.1.1]), we obtain a random family of compact self-adjoint positive operators Λ(ω) ∈ L(H), defined perfectly in ω, and satisfies…”
Section: Invariant Manifolds For Stochastic Models In Fluid Dynamicsmentioning
confidence: 99%
“…These manifolds are random objects and are perfectly defined for ω ∈ Ω. Using interpolation between discrete times and the (continuous-time) integrability condition (2.10), it can be shown that the above manifolds for the discrete-time cocycle (U (n, ·, ω), θ(n, ω)), n ≥ 1, also serve as perfectly defined local stable/unstable manifolds for the continuous-time cocycle (U (t, ·, ω), θ(t, ω)), t ≥ 0, near Y (ω) (see [16,19,22]). …”
Section: (Ii) (Iii)]) the Linearized Cocycle (Du (T Y (·) ·) θ(Tmentioning
confidence: 99%